2022
DOI: 10.3390/polym14112209
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity and Biodegradation of Sustainable Environment-Friendly Bone-Glue-Based Adhesive Suitable for Insulation Materials

Abstract: Bone glue with sodium lignosulfonate is a protein-based adhesive. Their combination leads to strong binding necessary for the achievement of adhesive properties. However, biodegradation and ecotoxicity of materials composed of bone glue and sodium lignosulfonate has never been studied before. In this paper, the biodegradation potential of the mixture of bone glue, lignosulfonate and rape straw modified by water or NaOH on an agar test with aerial molds and in acute aquatic tests with mustard, yeasts, algae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Concentrations of caffeine were 10 g or 20 g/L, copper and corundum concentrations were 20 or 40 g/L. These concentrations were selected on the basis of previous toxicity data with molds and fungi [5][6][7][8][9] or according to experience with the preparation of studied composite flax materials (Brejcha, personal communication).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations of caffeine were 10 g or 20 g/L, copper and corundum concentrations were 20 or 40 g/L. These concentrations were selected on the basis of previous toxicity data with molds and fungi [5][6][7][8][9] or according to experience with the preparation of studied composite flax materials (Brejcha, personal communication).…”
Section: Chemicalsmentioning
confidence: 99%
“…In recent years, the use of natural matrices of plant origin in building materials has been growing (kenaf, wood, hemp, coconut, cane and straw) [1][2][3][4][5][6]. One of such straw/s material is linen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the use of natural matrices of plant origin in building materials has been growing (kenaf, wood, hemp, coconut, cane and straw) [1][2][3][4][5][6][7]. One of such straw material is a flax.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of the increased environmental awareness of the last decades, which led to a renewed interest in natural materials, a few modern studies can be found on the use of animal glue as surface treatment for conservation, 12 or as sustainable glue for lignocellulosic materials or mineral materials. These lignocellulosic materials were used for compression moldable wood particle boards, 25 rapeseed straws, 26 peat moss, 27 and 3D printable wood. 28 While the mineral materials were utilized for the casting of asphalt, 29 lime mortars, 30 or calcium sulfate, 31 and in concrete 3D printing.…”
Section: ■ Introductionmentioning
confidence: 99%